Proces twórczy – droga kształtowania tożsamości artysty - Rodziński, Stanisław (Horyzonty Wychowania, 2017)
The text is the fruit of reflection concerning artistic creation,especially of the phenomenon colloquially referred to as the creativeprocess. People have been interested in arts for centuries,which entailed the interest in the artist himself, in his life, environment,the origin of his creative passions. When the artists beganto sign their works, when they started to reveal the authorship oftheir creation, this interest became something natural, thoughtoday it seems – awash with gossip, it, not infrequently, exceedsthe size of the work and the artist himself. Looking at the selfportraitsof Rembrandt or Van Gogh – but also reading autobiographical literature – we realize that there is no work of art, nosignificant work of art, in which the whole range of the creator’sprivacy, his times and most important issues would be discarded.In fine arts, as well as in literature, poetry, and music – encounteringa piece of work – we do encounter the man. Thisencounter sometimes induces the search for knowledge aboutthe artist, his methods of work, his lifestyle, dramas and joys thatsurrounded him. In his „Letter to the Artists”, John Paul II touchedupon this problem writing that the history of art does not constitutethe mere history of works of art, but it also refers to thepeople. In this way, we come to a point in which the knowledgeof the work of art involves the knowledge of the artist.